Iterative Schemes for Triequilibrium-Like Problems - Misbah Iram Bloach; Muhammad Aslam Noor; Khalida Inayat Noor (International Journal of Analysis and Applications, 2021)
In this work, we present a new class of equilibrium problems, termed as triequilibrium-like problems with trifunction in invexity settings. Classical varilunational-like inequalities and equilibrium-like problems can be obtained as specific variants of triequilibrium-like problems. Certain new iterative methods are proposed and examined for the solution of triequilibrium-like problems by using auxiliary principle technique. Convergence analysis of these proposed methods is examined under some mild conditions.